Parallel factorizations of polynomial matrices - Petrichkovich , V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
Conditions are established under which suggested factorizations of polynomial matrices over a field are parallel to factorizations of their canonical diagonal forms. An existence criterion of these factorizations of polynomial matrices is indicated and a method of constructing them is suggested.